Antiplasmodial Activity of Methanolic Extract of Asparagus officinalis L. Stem on Plasmodium berghei Infected Mice: Antiplasmodial Activity of Asparagus officinalis L. - Minari, Joseph Bamidele; Odutuga, Adewale. Agboola; Bamisaye, Fisayo Abraham; Babatola, Leye Jonathan (Biological Sciences - PJSIR, 2016)
This study aims at investigating the antiplasmodial activity of methanolic extract of Asparagus officinalis L. stem on Plasmodium berghei infected mice. To investigate this, the mice were infected with P.berghei to cause malaria. The mice were simultaneously given oral doses (20, 40 and 60 mg/kg body weight) of methanolic extract of A. officinalis L. stem. The phytochemical constituents of the extract revealed the presence of alkaloids, phenolics, cardiac glycosides, flavonoids, terpenoid and steroid. The extract administered to the infected mice significantly suppressed the parasite. The extract also significantly (P<0.05) reduced the activities of serum aspatate aminotransferase (AST), alkaline phosphate (ALP), alanine aminotransferase (ALT). White blood corpuscles (WBC), red blood corpuscles (RBC), hemoglobin (HGB), packed cell volume (PCV), platelets (PLT) and the mean corpuscular hemoglobin concentration (MCHC) showed significant (P<0.05) increase after the administration of the extract while mean corpuscular volume (MCV) and the mean corpuscular hemoglobin (MCH) showed significant (P<0.05) reduction. Present findings suggests that the plant extract contains phytochemicals that have antiplasmodial and hepatoprotective properties.